What do bankers think about halal financial services? / Zaimy Johana Johana and Mohd Zainee Hussain. - Johan, Zaimy Johana; Hussain, Mohd Zainee (Universit Teknologi MARA Cawangan Selangor, 2019)
Over the past three decades, Malaysian halal financial services have become one of the fastest growing industries with a range of products and services accepted by both Muslims and non-Muslims. However, the Islamic financial products and its Islamic banking institutions are facing stiff competition from conventional products in relation to marketing coverage, branding, product packaging and other pivotal aspects such as product features, benefits and advantages. Moreover, there is an immense pressure on the institutions to remain competitive along with the national goals of building shariah-driven ecosystem within the halal industry. Against the backdrop of the competitive financial industry landscape, this qualitative study examines the crucial attributes of Islamic financial services with focus on knowledge, attitude and level of acceptance of bankers in promoting, marketing and selling Islamic financial products and services. Employing semi structured interview technique; customer service officers of seven banks within Kuala Lumpur City Centre were selected. This exploratory study is aimed to identify the perception of bankers towards halal financial services and the study has discovered bankers' knowledge, attitude and level of acceptance of specific products can generate customer’s positive perception, awareness and acceptance of the product offered which will increase their satisfaction and loyalty. This study is expected to promote knowledge advancement and understanding of Islamic financial services towards fostering a healthy and complete offering of shariah compliant financial solutions. It can later further expand the asset base and outreach of the Islamic financial industry, and subsequently contributes towards increased customer satisfaction and loyalty.